POLICY IMPLEMENTATION AND INFORMATION SYSTEMS FOR PERSONS WITH DISABILITIES IN ENHANCING EMPLOYMENT OPPORTUNITIES IN DELI SERDANG REGENCY - Nabila Fahira Nasution; Tunggul Sihombing; Noverman Duadji (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This study examines the implementation of disability employment policy in enhancing employment opportunities for persons with disabilities in Deli Serdang Regency. A qualitative descriptive approach with a case study design was employed, with data collected through observation, interviews, and document analysis. The findings reveal that policy implementation has not yet been fully effective, despite Deli Serdang Regency Regulation No. 6 of 2020 mandating a 2% employment quota in government institutions and regional state-owned enterprises and a 1% quota in private companies. Key challenges include the absence of accurate disability employment data, weak quota compliance monitoring, limited workplace accessibility, insufficient stakeholder coordination, and persistent employer stigma. Critically, the study identifies the lack of an integrated disability employment information system as a structural gap that prevents evidence-based monitoring and policy evaluation. Using Grindle’s policy implementation framework, these challenges reflect weaknesses in both the content of policy and context of implementation dimensions. The study concludes that effective inclusive employment requires regulatory support alongside a dedicated information system connecting disability registration, employment placement, employer compliance, and training outcomes, stronger monitoring mechanisms, and cross-sector collaboration.